Main Features of Modern Technological Development - Poliakova, Julia (Bulletin of Yerevan University G: Economics, 2016)
The article is devoted to the definition of modern characteristics of the technological development of the countries in the era of technological globalization. The stages of the economic and technological paradigm are considered, the trends in the development of the market of scientific, technical and innovative products are identified. The article displays ways of applying technological strategies in different countries of the world and demonstrates an innovative long-term trend of world development.
Keywords: technological globalization, innovation, technologies, technological mode, technological strategy, technological development, top technologies